2019
DOI: 10.2116/analsci.18p532
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine B Chemiluminescence Improved by Mimetic AuCu Alloy Nanoclusters and Ultrasensitive Measurement of H2O2, Glucose and Xanthine

Abstract: The less stability and robustness, high-cost preparation and maintenance of natural enzymes, especially horseradish peroxidase (HRP), challenge researchers to introduce effective alternatives for their wide applications. Herein, the peroxidase-like activity of AuCu bimetal nanoclusters (AuCu NCs) was investigated in the rhodamine B-H2O2 chemiluminescence (CL) system. AuCu NCs could effectively catalyzed the CL reaction, and a high intensive emission intensity was obtained. A comprehensive study was implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…As a potent CL system, the RhoB–H 2 O 2 reaction was utilized for the investigation of the catalytic action of prepared CoMOF. This reaction is a well-known CL system with a weak emission, which can be intensified by application of suitable nanocatalysts. , On the other hand, cobalt-based catalysts have a good potential to improve the speed of H 2 O 2 -based CL reactions. , The great positive effect of Co-based catalysts has been described as the ability of cobalt­(II) to react with H 2 O 2 (reaction ) that leads to the formation of hydroxyl radicals (OH • ) . Subsequently, these radicals can mainly follow two mechanisms: (1) they can react with each other and produce the excited double oxygen ((O 2 ) 2 *; reactions –), leading to the generation of CL emission in the wavelength range of 450–550 nm; (2) due to the high oxidizing behavior of OH • , they can react with other organic or inorganic CL reagents and facilitate their oxidation. Herein, it was observed that the CL emission of the RhoB–H 2 O 2 system was remarkably enhanced in the presence of CoMOF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potent CL system, the RhoB–H 2 O 2 reaction was utilized for the investigation of the catalytic action of prepared CoMOF. This reaction is a well-known CL system with a weak emission, which can be intensified by application of suitable nanocatalysts. , On the other hand, cobalt-based catalysts have a good potential to improve the speed of H 2 O 2 -based CL reactions. , The great positive effect of Co-based catalysts has been described as the ability of cobalt­(II) to react with H 2 O 2 (reaction ) that leads to the formation of hydroxyl radicals (OH • ) . Subsequently, these radicals can mainly follow two mechanisms: (1) they can react with each other and produce the excited double oxygen ((O 2 ) 2 *; reactions –), leading to the generation of CL emission in the wavelength range of 450–550 nm; (2) due to the high oxidizing behavior of OH • , they can react with other organic or inorganic CL reagents and facilitate their oxidation. Herein, it was observed that the CL emission of the RhoB–H 2 O 2 system was remarkably enhanced in the presence of CoMOF.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction is a well-known CL system with a weak emission, which can be intensified by application of suitable nanocatalysts. 40,41 On the other hand, cobalt-based catalysts have a good potential to improve the speed of H 2 O 2based CL reactions. 42,43 The great positive effect of Co-based catalysts has been described as the ability of cobalt(II) to react with H 2 O 2 (reaction 1) that leads to the formation of hydroxyl radicals (OH • ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3 New typical nanozymes such as metal-based functional materials have advantages in synthesis, purification, storage and stability in vitro (vivo) and sensitivity examinations. [4][5][6] Also, there are existing issues with natural enzymes in synthesis, isolation and purification, and their stability is poor under harsh pH and temperature conditions. Since iron oxide NPs were first reported to have peroxidase activity, nanomaterials have been explored for their enzymatic activity, including those made with metals, alloys, metal oxides, composites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, xanthine, a metabolite of adenine and guanine in most human body tissues and fluids, and its abnormal level in the body results in many diseases including hyperuricemia and gout . Hence, developing a sensitive method for determining xanthine content is very significant. Because H 2 O 2 is the product of the xanthine oxidase (XOD) catalyzing xanthine, many peroxidase-like mimics were used to detect xanthine content, such as Fe, N-CDs, Se- g -C 3 N 4 nanosheets, and iridium nanoparticles . Note that there have been few studies on MOFs to detect xanthine based on its peroxidase-like properties, so by employing MIL-3DG- n as peroxidase mimics, a rapid, sensitive, and convenient fluorescent biosensor for xanthine was realized.…”
Section: Introductionmentioning
confidence: 99%